Analisis Faktor Kredibilitas Website E-Commerce Indonesia Studi pada Online Purchasing - Cordiaz, Muhammad; Prahasto, Toni; Widiyanto, Ibnu (Universitas Diponegoro, 2013)
In the number of Internet users in Indonesia continues to increase. Internet increasingly being used for purchasing online. There are many e-commerce websites that offer goods and services online. Internet users should be able to distinguish which websites are credible before engaging in electronic commerce activities. Be an interesting question, what factors are rated by visitors of a website as an e-commerce website that is credible or reliable. Using a web-based survey methods, respondents were asked what factors support the credibility of the website in electronic commerce purchasing transactions. The respondents were Internet users. Proposed survey questions are grouped into four factors, namely, kerpercayaan factors, factors expertise, sponsorship factors and specific factors. The survey results were tested with descriptive statistic. Based on the data obtained, the Trust Factor respondents prefer e-commerce website that is trusted by his close associates, while the respondents assess the Skill Factor of websites that apply when payments online transactions through banks Indonesia is considered more reliable. In the Sponsorship Factor and Specific Factor, respondents believe the e-commerce website that does television ads in the media and managed by official institutions. Keywords : credibility, trustworthiness, expertise, electronic commerce, online purchasing